Avaliação da usinagem do INCONEL 718 - Santos Junior, Tarcisio Antunes dos [UNESP] (2011)
The nickel superalloys are known as being a material with poor machinability, they have some properties like high hardness, good resistance at high temperature, tendency to weld with the tool material at high temperature, etc. In the aerospace, biomedical and petrochemical industry, are increasing the need to use materials that resist to aggressive process and environment. In these uses, it has increased the use of nickel-based superalloys like Inconel 718 and consequently the need to research new techniques and tools to improve the machinability of this material. For the superalloys and resistant alloys at high temperatures is considered that the difficulty in the machining regards to the combination of the relatively high cutting forces and high temperatures that grow during the machine process, causing deformation or breakage of the cutting tool. This work purpose is to develop the study of the machining of external cylindrical turning of the nickel based alloy Inconel 718, using ceramic tools, seeking the optimization of machining this alloy, looking to provide real productive increases without the need of investments in new production means. The machining test were accomplished using commercials hard metal tools and the results were compared each other to find the best tool and the best parameter. The conclusion is that the tool TNMG160408-23 -class 1005- was the better one, when used with the parameter 60_15_08